Digital Marketing as a Strategy to Defend MSMEs in the Covid-19 Pandemic - Danang Satrio; Ari Muhardono (FIRM Journal of Management Studies, 2022)
MSMEs actors are deemed to lack resilience and flexibility in facing the Pandemic due to several things such as the low level of digitization, difficulties in accessing technology and a lack of understanding of survival strategies in business. Basically, MSMEs actors must be able to survive and adapt to existing business developments because businesses that can survive are businesses that are responsive to the times. The use of digital marketing by MSMEs players has the potential to help MSME players in marketing their products during a pandemic. Digital marketing intends to initiate and circulate online information about the user's experience in consuming a product or brand, with the main goal of engaging the community. In doing digital marketing, MSMEs players are required to always learn and think openly to increasingly developing technology. Of course, digital marketing also considers using suitable media and the right way of communication that is tailored to the selected segment or market share. So that marketing will be more effective and not wrong target.